PENENTUAN LOKASI DAN JALUR EVAKUASI TSUNAMI DI KABUPATEN CIANJUR JAWA BARAT - Danly Souhuwat; Rahel Situmorang; Herika Muhamad Taki (Jurnal Lingkungan dan Kota, 2021)
The villages of Sukapura, Cisalak, and Jayapura in Cidaun Subdistrict, Cianjur Regency, West Java are three of the 584 villages on the south coast of Java which are very prone to tsunamis with a high hazard class. In the 2011-2031 Cianjur Regency Spatial Plan, the area designated as the site and route for tsunami evacuation is very far from the villages of Sukapura, Cisalak and Jayapura. The purpose of this study was to identify the site and route of tsunami evacuation in the three village areas. The method used in this research is tsunami run-up modeling with a model builder to measure the tsunami inundation area. Determination of tsunami evacuation sites uses overlay analysis, while determining tsunami evacuation routes uses network analysis. The results of this study, there are 17 tsunami evacuation sites and 5 tsunami evacuation routes to the nearest evacuation location in each village area. The research is expected to provide an overview for the local community and advice for the government in order to increase awareness and mitigate tsunami disasters.